Chicken, pig, cow's first fight - Ohi, Ruth (Ohi, Ruth. Ruth Ohi picture book., 2012)
When Girl builds a block city, Chicken makes it perfect by adding a statue. Along comes Pig, zipping, zapping, and zooming--until he smashes into Chicken's statue, destroying it--and the city. He gets angry and goes off in a huff. Will the friends be able to put the city together again, and will they be able to rebuild their friendship?